Occurrence and Molecular Characterization of Cryptosporidium Infection in HIV/Aids Patients in Algeria - Malika Semmani; Damien Costa; Nassima Achour; Meriem Cherchar; Hanifa Ziane; Abdelmounaim Mouhajir; Venceslas Villier; Haiet Adjmi Hamoudi; Loic Favennec; Romy Razakandrainibe (Viruses, 2023)
The estimated prevalence rate of adults living with HIV infection in MENA is one of the lowest in the world. To date, no data on the genetic characteristics of Cryptosporidium isolates from HIV/AIDS patients in Algeria were available. This study aimed to identify Cryptosporidium species and subtype families prevalent in Algerian HIV-infected patients and contribute to the molecular epidemiology mapping of Cryptosporidium in the MENA region. A total of 350 faecal specimens from HIV/AIDS patients were analysed using microscopy, and a Cryptosporidium infection was identified from 33 samples, with 22 isolates successfully sequencing and confirming species and subtypes. Based on sequence analysis, 15 isolates were identified as C. parvum with family subtypes IIa (n = 7) and IId (n = 8), while five were identified as C. hominis (family subtypes Ia (n = 2) and Ib (n = 3)) and two as C. felis. The C. parvum subtype families IIa and IId predominated, suggesting potential zoonotic transmission. More extensive sampling of both humans and farm animals, especially sheep, goats and calves, as well as a collection of epidemiological data are needed for a better understanding of the sources of human C. parvum infections in Algeria.